Frequency of Hyponatremia in Children Admitted with Pneumonia - Adnan, Mian Sohail; Bibi, Nafeesa Bibi; Noor Ul Bashar; Anees, Aleena Anees; Zahid, Masroor; Khan, Muhammad Sohaib (Indus Journal of Bioscience Research, 2025)
Objectives: The purpose of this study was to establish the prevalence of hyponatremia among children of 2 months to 5 years of age admitted at Ayub Teaching Hospital, Abbottabad, with pneumonia and factors related to it. Materials and Methods: An analytical cross-sectional study was conducted in the pediatric department on 135 children with pneumonia. The level of hyponatremia was determined by the patient’s serum sodium concentration <135mEq/L, moderate 131-134mEq/L, severe 126-130mEq/L, and severe 125mEq/L. The socio-demographic profile of the children, the severity of pneumonia, and data on socio-economic status were obtained. All statistical analyses were done using the statistical package SPSS. Results: In this study, 28% of the children had hyponatremia, 14% mild, 9% moderate, and 5% severe hyponatremia. In general, a higher incidence was reported in severe pneumonia (40%) among children 2-3 years old and low economic status. There were few differences between males and females. Conclusion: A recent study shows that hyponatremia is highly prevalent in childhood pneumonia and that the prevalence is related to illness severity, age, and socio-economic status. More awareness, earlier presentation, and proper management would significantly enhance the outlook.